2006
DOI: 10.1007/s11046-006-0029-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antifungal Susceptibility of Yeasts Obtained from the Oral Cavity of Elderly Individuals

Abstract: Infections caused by Candida yeasts are common in elderly individuals. Seventy-five isolates of Candida spp. were obtained from saliva samples of 136 institutionalized elderly individuals resident in six retirement homes of Belo Horizonte, Brazil. Forty-seven isolates (62.66%) were identified as Candida albicans, 15 (20%) as C. tropicalis, 7 (9.33%) as C. glabrata, 4 (5.33) as C. parapsilosis, and 2 (2.67%) as C. guilliermondii. Among the 136 elderly individuals studied, 49 (36%) were male and 87 (64%) were fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 22 publications
6
48
2
2
Order By: Relevance
“…In addition, non albicans species ( C. parapsilosis , C. krusei and C. kefyr ) were more frequently (p < 0.01) after the treatment. C. tropicalis was not isolated from the patients of this study, differing from other researchers that obtained this species as the second most common in oral cavity (13). Erköse and Erturan (3) found that C. albicans was the most frequent isolated from patients infected with human immunodeficiency virus, corresponding to 82.8% of the studied patients.…”
Section: Resultscontrasting
confidence: 90%
See 1 more Smart Citation
“…In addition, non albicans species ( C. parapsilosis , C. krusei and C. kefyr ) were more frequently (p < 0.01) after the treatment. C. tropicalis was not isolated from the patients of this study, differing from other researchers that obtained this species as the second most common in oral cavity (13). Erköse and Erturan (3) found that C. albicans was the most frequent isolated from patients infected with human immunodeficiency virus, corresponding to 82.8% of the studied patients.…”
Section: Resultscontrasting
confidence: 90%
“…On the other hand, Resende et al . (13) and Oksuz et al . (11) obtained C. albicans isolation from 62.66% and 66.4% of the patients from their works.…”
Section: Resultsmentioning
confidence: 96%
“…samples obtained from healthy individuals, with no signs of oral candidiasis. Several studies have reported the prevalence and antifungal susceptibility testing in individuals with oral candidiasis manifestations (2,4,10,14), but only a few studies have focused on samples obtained from Candida carriers without signs of infection (21).…”
Section: Discussionmentioning
confidence: 99%
“…Candida albicans is the yeast species most frequently found in isolates; the other yeasts encountered are: Candida tropicalis, Candida krusei, Candida guilliermondii, Candida stellatoidea, Candida parapsilosis and Candida glabrata 5 . Yeast infections often affect the elderly [5][6][7][8] . Moreover, some authors 9 have shown a significant association between mouth colonisation and infection by yeasts.…”
Section: Introductionmentioning
confidence: 99%